Static and dynamic impacts of shunt capacitor placement in distribution systems - Rafidah, Abdul Kadir (2009)
Adding capacitors to power system distributions provides well known benefits, including power factor correction, voltage support and increase of active power transfer capacity. This thesis will presents the static and dynamic impacts of shunt capacitor placement in distribution systems by describes measurements and studies performed before and after the installation of 49.46MVAr capacitor banks in 4-bus test system and a 37.92MVar capacitor banks in-9 bus test systems. A load flow analysis is conducted to predict power flow magnitudes, power factor, voltage levels and losses in branches of the system. The results are used to determine the size of capacitor banks to maintain an acceptable power factor and or voltage level to measure the power losses before and after capacitor bank installation. The fault analysis also been studied by applying single line to ground fault to see the impacts when fault applied before and after installation of capacitor bank since most of researcher did not include the capacitors in fault studies. Switching transients analysis were also studied since the capacitor switching transient can be very damaging and costly problems where the transient voltage on the power system causes the power and voltage flows in the system to change from the steady-state value. Thus in order to take appropriate pre-cautions in real system, it is necessary and advantageous to analyze and determine the worst case switching transients before the actual switching take place. In this thesis, 2 test systems which were developed for power flow analysis was used to examine characteristics of transient voltage by using 3 set of different size of capacitor bank. The basic fundamental method to reduce the transient voltage also been investigated. The results of measurements are compared to the ones obtained by studies and simulations. The modeling and transient simulation were carried out by using MATLAB and PSCAD software.